Mapping of Stakeholders in the Development of Coastal Areas Based on Blue Economy in Bima City - Nurfallah, Iip; Fajar Saputra, Muhamad (Green Publisher Indonesia, 2025)
The concept of the blue economy provides opportunities to harness the potential of marine resources in a sustainable manner, but its implementation often faces challenges. This study aims to map stakeholders in the management of coastal areas based on the blue economy in Bima City, West Nusa Tenggara, in order to overcome challenges such as conflicts of interest and unsustainable resource exploitation. Through a qualitative approach that includes interviews and analysis of documents, the study identifies three categories of stakeholders: core, supportive, and contextual ones. The analysis of the power-interest matrix shows the importance of strategic collaboration between stakeholder groups to create inclusive and sustainable blue economic governance. Research recommendations include the establishment of dialogue forums, technical training, private sector partnerships with communities, and strengthening the role of NGOs in supporting environmental sustainability, community welfare, and local economic growth.